PERCEIVED ROLES OF MEN AND BOYS IN ENDING GENDER BASED VIOLENCE IN NIGERIA - Dike, Oluchi.G.; Chukwuka, Nwamaka. N.; Chinonso, Ugochukwu Dandy (African Journal of Social and Behavioural Sciences, 2026)
Gender-Based Violence (GBV) continues to be a widespread and persistent challenge in Nigeria, with high prevalence and widespread awareness. It is a multidimensional issue that intersects with critical global development concerns and transcends generations. While women and girls are the primary victims, men and boys are often identified as key perpetrators who may also be engaged as important stakeholders in efforts to prevent and address GBV. This study examines the perceived roles of men and boys in the mitigation of GBV in Nigeria, highlighting their potential as allies and agents of change. Using a cross-sectional survey design, data were collected from 269 male respondents (167 men and 102 boys) aged 14-64 years (M = 41.39) using convenience sampling. Data were gathered using a self-developed questionnaire disseminated online via Google Forms across social media platforms and offline (to accommodate those without internet access). The instrument was subjected to face and content validation and demonstrated acceptable internal consistency (Cronbach’s α = 0.86). Six hypotheses related to GBV awareness and intervention roles were tested. Chi-square analysis indicated a high level of GBV awareness among respondents and identified key perceived roles of men and boys in addressing GBV. These included promoting positive masculinity, fostering education and awareness, demonstrating empathy and emotional intelligence, participating in advocacy efforts, and serving as role models. The findings suggest that these roles are perceived as important components of GBV prevention and response efforts. The study recommends the strengthening and integration of these roles within existing prevention and intervention frameworks. It also highlights the need for future research to explore specific behavioral and socio-cultural factors, such as silence, stigma, gaslighting, and bread-crumbing, that may be associated with the persistence of GBV, thereby providing deeper insight into culturally embedded practices and attitudes.